Investigating the macroeconomic determinants of RDP house prices in South Africa - Avramis, Nicholas (Research of GSB, 2017)
The main purpose of this study is to investigate the relationship between macroeconomic variables and South Africa's affordable housing market using basic multivariate regression analysis. This paper empirically examines whether increases in RDP house prices can be explained by or attributed to the movements in gross domestic product (GDP), prime lending rate (RATE), the stock market (JSE) and inflation (CPI). As an exploratory paper in nature, data of RDP resales prices from eight major metropolitan cities in South Africa was collected from the Centre of Affordable Housing Finance (CAHF) for the period 2007 to 2015. The findings from the regression analysis show that only JSE is a key determinant of RDP housing prices in South Africa. Since there was no a statistically significant relationship that could be found between affordable housing price movements and GDP, RATE and CPI, this study suggests that hedonic variables should be used in future studies, as well as accounting for regional differences. Notwithstanding, since the resale of RDP homes is a new dimension in the real estate market and whose introduction is also still at its infancy in South Africa, an examination of the RDP home prices is important to the financiers (financial institutions), investors, housing authorities, the government and other interested stakeholders who might want to have an understanding of the factors that drive the prices of these homes in South Africa. The results from this study, therefore, play a role in informing these parties as they allow them to make better decisions in terms of whether to make financing available (financial institutions), policy formulation or direction (government) and whether to invest or sale (other stakeholders).